Socio-Demographic Risk Factors for Severe Acute Malnutrition (Jalalabad Medical Journal, 2025)
Malnutrition is one of the leading causes of morbidity and mortality in under-five children in developing countries. Bangladesh being one of the developing countries, malnutrition is an important public health problem. This was a hospital-based case-control study conducted in the department of Paediatrics, Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet during the period from July 2013 to June 2014 to see the socio-demographic risk factors for severe acute malnutrition among children under five. Forty-five severe acute malnourished children, aged 6 months to 5 years, with a weight-for-height Z score below -3 were enrolled in the case group. Controls were age and sex matched, well-nourished children with a weight-for-height Z score of -1 to